A Concise Review of the Popularised Drugs Used For The Management of COVID-19 (SARS-CoV-2) - Ahmad, Arghal; Sheikh, Hafsa (Archives of Clinical and Biomedical Research, 2020)
Background: Coronavirus disease 2019 (COVID-19) caused by SARS-COV-2 has been largely associated with many different therapeutic agents (both homeopathic & pharmaceutical) by the media and the general public but there is little evidence-based published material to support their claims. The purpose of this article is to provide a comprehensive review of the various therapeutic agents used for the treatment of COVID-19 which have been lauded by the media and the general public. Method: We conducted an in-depth review of the various case reports and retrospective clinical studies published on the therapeutic measures, both homeopathic and pharmaceutical, used for the management of COVID-19 using PubMed and Google Scholar as our primary sources. We analyzed the real-life implications of alternative therapies such as Ayurveda and Pranayama and herbal medications such as Sana Makki and Sangju yin being used as a form of prophylaxis, and add-on treatments. We’ve also assessed the therapeutic effects of various pharmaceutical agents currently being used in the management of COVID-19 and other drugs that have been popularized by various news outlets and social media. Conclusion: Research is still ongoing on the various drugs used in the management of COVID-19. Caution has to be taken when introducing a new medication into treatment regimens, whether it is allopathic or homeopathic, without proper evidence despite pressure from the media and/or the patients. As mismanagement can further strain the overwhelmed healthcare system. Patient and general public education should take precedence as no drug is a cure-all for this novel virus. New updates come every day and treatment protocols are refined throughout the world thanks to the flow of information and the joint effort of researchers and clinicians.